2016
DOI: 10.5751/es-08495-210241
|View full text |Cite
|
Sign up to set email alerts
|

Learning from one another: evaluating the impact of horizontal knowledge exchange for environmental management and governance

Abstract: . 2016. Learning from one another: evaluating the impact of horizontal knowledge exchange for environmental management and governance. Ecology and Society 21 (2) ABSTRACT. There is increasing advocacy for inclusive community-based approaches to environmental management, and growing evidence that involving communities improves the sustainability of social-ecological systems. Most community-based approaches rely on partnerships and knowledge exchange between communities, civil society organizations, and professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Recently Tschirhart et al (2016) confirmed that peer to peer learning is effective and that effort should be put into identifying, and then strengthening, community owned solutions through peer-to-peer knowledge exchange. Policy, Social, and Actor Network Analysis (Jackson, 2010;Brockhaus et al, 2014;Gallemore et al, 2015) coupled with Actor Network Theory (Valverde, 2007) can provide insight on where scientists can situate themselves to co-generate the knowledge that will influence narratives and behaviors.…”
Section: Science To Co-generate Knowledgementioning
confidence: 99%
“…Recently Tschirhart et al (2016) confirmed that peer to peer learning is effective and that effort should be put into identifying, and then strengthening, community owned solutions through peer-to-peer knowledge exchange. Policy, Social, and Actor Network Analysis (Jackson, 2010;Brockhaus et al, 2014;Gallemore et al, 2015) coupled with Actor Network Theory (Valverde, 2007) can provide insight on where scientists can situate themselves to co-generate the knowledge that will influence narratives and behaviors.…”
Section: Science To Co-generate Knowledgementioning
confidence: 99%
“…Patel and Mitlin (2002) declared that participation process is a transformational apparatus for social change, better decision and efficient services to the society. Participation in decision making provides avenues for cross-fertilization of idea (Tschirhart et al, 2016) as it enable the citizen acquires skills to challenge or persuade the government where necessary; and conversely, government persuades its citizens, builds trust and calm anxiety or hostility to strike a balance vis-à-vis give room for harmonious relationship with the citizens towards societal development .…”
Section: Theory Of Participationmentioning
confidence: 99%
“…The framework intends to be inclusive rather than exclusive, creating a type of nested community governance within the broader legal framework (Tschirhart et al 2016, Talbot-Jones 2017. Implementation of the Te Awa Tupua framework is supported through a series of payments to the river by the Crown, including a NZ$30 million contestable fund, Te Korotete o Te Awa Tupua, which can be used for the purposes of giving the rights of the river and its catchment force and effect.…”
Section: Case Study 1: the Rivers Of Victoria Australiamentioning
confidence: 99%